LAYANAN BIMBINGAN KARIR PADA PESERTA DIDIK YANG MEMILIKI PRESTASI DALAM AKADEMIK DI SMA PASUNDAN MAJALAYA - Lani Apriliani; Euis Eti Rohaeti; Tita Rosita (IKIP Siliwangi, 2020)
This research is motivated by the fact that there are still students who have achievements in school but have difficulty in preparing career planning. The form of efforts made in counseling guidance services to provide understanding of students in career planning, namely through career guidance services. This research was conducted with a qualitative research approach. The data collected in this study are data obtained by means of interviews, observation and documentation study. The subjects in this study were five students who had first rank academic achievement in the class. class XI bk teacher, and BK coordinator. The form of career counseling services at SMA Pasundan Majalaya begins with several stages, namely classical guidance, group guidance, and individual counseling.Keywords: Career Guidance, Career Planning, Academic Achievement